2016
DOI: 10.1038/nri.2016.99
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of p53 and other tumour-suppressor genes in immune regulation

Abstract: Tumour-suppressor genes are indispensable for the maintenance of genomic integrity. Recently, several of these genes, including p53, PTEN, RB1 and ARF, have been implicated in immune responses and inflammatory diseases. In particular, the p53 tumour-suppressor pathway is involved in crucial aspects of tumour immunology and in homeostatic regulation of immune responses. Other studies have identified roles for p53 in various cellular processes, including metabolism and stem cell maintenance. Here, we discuss the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
252
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(263 citation statements)
references
References 193 publications
(221 reference statements)
9
252
1
1
Order By: Relevance
“…As expected, intrathecal treatment with si-PUMA and PFT-α exerted similar effects on preventing increased p53 and caspase 3 protein expressions. Additionally, the broader role of p53 in integrating with inflammatory pathways via NF-κB transcription has been reported [11]. Consistent with our study, comparable anti-inflammatory effects were also observed in rats injected with si-PUMA and PFT-α, as similar preservations of BSCB integrity and decreased protein levels of NF-κB and cytokines IL-1β and TNF-α were observed.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, intrathecal treatment with si-PUMA and PFT-α exerted similar effects on preventing increased p53 and caspase 3 protein expressions. Additionally, the broader role of p53 in integrating with inflammatory pathways via NF-κB transcription has been reported [11]. Consistent with our study, comparable anti-inflammatory effects were also observed in rats injected with si-PUMA and PFT-α, as similar preservations of BSCB integrity and decreased protein levels of NF-κB and cytokines IL-1β and TNF-α were observed.…”
Section: Discussionsupporting
confidence: 92%
“…29 Nonetheless, it has become clear that p53 also participates in various aspects of immune modulation in cancer. 30 In the present study, we are reporting that introducing functional wtp53 gene via SGT-53 can induce immunogenic changes of cancer cells, effectively promote anti-tumor immunity, and reduce tumor-induced immunosuppression in the TME. By augmenting anti-PD1 immune checkpoint blockade, the SGT-53 was able to convert mouse syngeneic tumors that were relatively insensitive to anti-PD1 into tumors that were more responsive to anti-PD1 therapy.…”
Section: Discussionmentioning
confidence: 80%
“…5 Moreover, the use of p53 inhibitors, such as Pifithrin-β, has been approved in clinical trials to attenuate the side effects of chemotherapy. 9 Given the described adverse impact of disrupting p53 in TECs and in T cells,5 the therapeutic use of p53 inhibitors must be implemented with care to safeguard the balance between immune reconstitution and tolerance induction.…”
Section: A01/00mentioning
confidence: 99%
“…Yet recent studies have revealed alternative roles for p53 in immunoregulation and autoimmunity. 5 In relation to the thymic epithelium, the observations that the p53 homolog p63 controls the turnover of TEC progenitors 6 imply a possible functional relationship within the p53 family. The analysis of the role of p53 in TEC physiology has been precluded because of its broad expression pattern and the complex phenotype of germline p53-null mice, which ultimately develop thymic lymphomas.…”
mentioning
confidence: 99%